A Method of Calculating the Interaction Energy between Particles in Minerals Flotation. (21st April 2016) - Yao, J.; Han, H.; Hou, Y.; Gong, E.; Yin, W.
Abstract : Extended-DLVO (Derjaguin-Landau-Verwey-Overbeek) theory is applied to calculating the interaction energy between particles in flotation process in the paper. This study investigates and compares the floatability of magnesite, dolomite, serpentine, and quartz in single mineral flotation and artificial mixture flotation with DDA as collector. The results showed that when the pH, dissolved ions, and competitive adsorption had a minor influence on their floatability, fine magnesite and dolomite largely decreased the recovery of quartz. SEM analysis on the flotation products demonstrated severe masking of fine particles on the surface of quartz. The Extended-DLVO theory was applied to calculate the interaction energy between the minerals, and the results showed that the interaction forces between magnesite and quartz, serpentine and quartz, and dolomite and quartz were attractive; therefore, fine magnesite, serpentine, and dolomite particles are easily masked on the surface of quartz. The calculation results agree with the experiment results and explain the mechanism of particles interaction and the reasons for the inconsistency in single mineral flotation and actual ore flotation. The particles interaction behavior is important in flotation process, and the interaction energy calculation is helpful for evaluating this behavior.